2008
DOI: 10.2478/v10033-008-0008-6
|View full text |Cite
|
Sign up to set email alerts
|

Innovation Propensity in Croatian Enterprises: Results of a Community Innovation Survey

Abstract: This paper assesses the determinants of innovation activities in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 28 publications
0
19
0
3
Order By: Relevance
“…At the same time it should be mentioned that over the years the concept of innovation has changed towards more interactive, cumulative and cooperative phenomenon (Rothwell, 1992;Aralica, Račić, & Radić, 2005). Inter-organisational interaction and related external knowledge is believed to support innovativeness (Cohen, & Levinthal, 1990;Muller & Zenker, 2001).…”
Section: Regional Competitiveness As a Results Of Agglomeration Economiesmentioning
confidence: 99%
“…At the same time it should be mentioned that over the years the concept of innovation has changed towards more interactive, cumulative and cooperative phenomenon (Rothwell, 1992;Aralica, Račić, & Radić, 2005). Inter-organisational interaction and related external knowledge is believed to support innovativeness (Cohen, & Levinthal, 1990;Muller & Zenker, 2001).…”
Section: Regional Competitiveness As a Results Of Agglomeration Economiesmentioning
confidence: 99%
“…The underlying intuition is that flatter, decentralized organizations are more effective in realizing their goals (Zheng et al, 2010) and therefore a flatter organizational structure will be more conducive to innovation. Additional controls were included for other variables, such as size (Cohen, 2005), ownership (Aralica et al, 2008), staff qualifications and training (Romijn and Albaladejo, 2002), which have been identified as also affecting the potential for innovation. SIZE was measured as the logarithm of the number of employees in Appendix 2 contains a summary of all the variables described so far.…”
Section: Control Variables (Regression)mentioning
confidence: 99%
“…The resulting body of literature attempts to build a more thorough theoretical understanding of what works and what does not, and to validate practical interventions (see Keizer et al, 2002 andAralica et al, 2005 for systematic reviews). These studies revealed that activities directed towards innovation show a relationship with a considerable number of variables, the most common of which are firm size (Cohen, 2005); ownership ; age (Jung et al, 2003); geography (Hoffman et al, 1998); R&D (Birchall et al, 1996), staff characteristics (Romijn and Albaladejo, 2002); and collaboration with several actors like customers (Le Blanc et al, 1997), suppliers (Lipparini and Sobrero, 1994) and knowledge centres (Hoffman et al, 1998;Oerlemans et al, 1998).…”
Section: Introductionmentioning
confidence: 99%